Konsep Negara Dan Pemerintahan Dalam Perspektif Fikih Siyazah Al-Gazzali - Sahri, Sahri (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
As one of the most comprehensive Islamic thinkers in the realm of thought, al-Gazz?l? to be one of the points of references to Islamic thought in this day, including in this case is about the concept of state and government. This article wants to show the wealth of thought of al-Gazz?l? relates to state and government. According to al-Gazz?l?, the political power and religion has a very strong interdependence. This case he is expressed in terms of ad-d?n as?s wa a?-?ul??n h?ri? (religion as a basis and sultan or the country as a protector). Thus, al-Gazz?l? firmly stated that the construct of the state and the government is demand of religion (min dar?riyy?t asy-syar’i) that can not be ignored (l? sabi?la il? tarkih). Furthermore, in this article, showed that al-Gazz?l? considers the Imamate or the government is a successor of the Prophet. It’s because of his function that inheren with the religious issues, so the caliph in running his government is regarded as a saint (muqaddas). About the source of authority of power, alGazz?l? considers that it is not a God given (theocracy) but by the support of the wider community represented by people who are influential (‘ahl asy-syawka) and followed by other people. Al-Gazz?l? stressed that the rise and fall of a ruler depends entirely to the presence and absence of support from the community (Muslims). So, in this case, al-Gazz?l? is differ with the mainstream paradigm of Shiite and also does not have a fatalistic paradigm (Jabariyah).